Utility of ultrasound elastography in a cohort of patients with idiopathic carpal tunnel syndrome - Doaa M. Emara; Mohamed M. El Shafei; Hoda M. Abdel Naby (The Egyptian Journal of Radiology and Nuclear Medicine, 2018)
Objective: The aim of this study was to assess the accuracy of ultrasound elastography as a recent imaging technique in diagnosis of CTS and evaluation of its severity in patients suffering clinically compared to the results of the gold standard electrophysiological tests. Materials and methods: This was a prospective cross sectional study included 100 patients clinically diagnosed as having unilateral idiopathic CTS (90% of the dominant hand), referred to radiology department from physical medicine department at Alexandria main university hospital from June 2015 till May 2016 after being evaluated electrophysiologically for correlation with the data of the ultrasound and ultrasound elastography of the median nerve. A control group of 100 patients with no wrist or hand complain were included in the study. Results: As diagnosed electrophysiologically, there were 44 (44%), 35 (35%) and 21 (21%) patients with mild, moderate and severe degree of CTS respectively. The mean cross sectional area of the median nerve among the studied cases was 12.19 ± 1.59 mm2 while the mean strain ratio of the median nerve by ultrasound elastography was 2.20 (1.0–5.0). Conclusion: In addition to electrophysiological study, ultrasound and ultrasound elastography are valuable tools for the diagnosis and classification of CTS.